2012
DOI: 10.1101/cshperspect.a011726
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology and Clinical Manifestations of the  -Thalassemias

Abstract: The b-thalassemia syndromes reflect deficient or absent b-globin synthesis usually owing to a mutation in the b-globin locus. The relative excess of a-globin results in the formation of insoluble aggregates leading to ineffective erythropoiesis and shortened red cell survival. A relatively high capacity for fetal hemoglobin synthesis is a major genetic modifier of disease severity, with polymorphisms in other genes also having a significant role. Iron overload secondary to enhanced absorption and red cell tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
122
0
17

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(140 citation statements)
references
References 107 publications
1
122
0
17
Order By: Relevance
“…Iron deposition in the parenchymal tissues of thalassemia patients can be observed within a year of the onset of regular blood transfusions [33]. Studies have shown that iron gets accumulated in the cardiac, endocrine, hepatic tissues and gingivae of thalassemia major patients [34,35]. While the impact of iron deposits on periodontal health is unidentified, more studies investigating the use of gingival biopsies for the diagnosis of iron overload are required.…”
Section: Dental Infectionsmentioning
confidence: 99%
“…Iron deposition in the parenchymal tissues of thalassemia patients can be observed within a year of the onset of regular blood transfusions [33]. Studies have shown that iron gets accumulated in the cardiac, endocrine, hepatic tissues and gingivae of thalassemia major patients [34,35]. While the impact of iron deposits on periodontal health is unidentified, more studies investigating the use of gingival biopsies for the diagnosis of iron overload are required.…”
Section: Dental Infectionsmentioning
confidence: 99%
“…And after many years of failure, promising approaches to somatic cell gene therapy for thalassemia have been reported, and trials are likely in the near future. It is beyond the scope of this article to review these issues in detail, several of which have been the subject of recent reviews (41,62,63,97).…”
Section: Further Progressmentioning
confidence: 99%
“…Moreover, a-and non-a-globin synthesis must be closely matched. As explained in Nienhuis and Nathan (2012), subunit imbalance is central to the pathophysiologyof the thalassemias. Free a-globin subunits are particularly toxic to erythroid cells.…”
mentioning
confidence: 99%